A specialized protocol for mechanical testing of isolated networks of type II collagen. (December 2022) - Szarek, Phoebe; Pierce, David M.
Abstract: The mechanical responses of most soft biological tissues rely heavily on networks of collagen fibers, thus quantifying the mechanics of both individual collagen fibers and networks of these fibers advances understanding of biological tissues in health and disease. The mechanics of type I collagen are well-studied and quantified. Yet no data exist on the tensile mechanical responses of individual type II collagen fibers nor of isolated networks comprised of type II collagen. We aimed to establish methods to facilitate studies of networked and individual type II collagen fibers within the native networked structure, specifically to establish best practices for isolating and mechanically testing type II collagen networks in tension. We systematically investigated mechanical tests of networks of type II collagen undergoing uniaxial extension, and quantified ranges for each of the important variables to help ensure that the experiment itself does not affect the measured mechanical parameters. Specifically we determined both the specimen (establishing networks of isolated collagen, the footprint and thickness of the specimen) and the mechanical test (both the device and the strain rate) to establish a repeatable and practical protocol. Mechanical testing of isolated networks of type II collagen fibers leveraging this protocol will lead to better understanding of the mechanics both of these networks and of the individual fibers. Such understanding may aid in developing and testing therapeutics, understanding inter-constituent interactions (and their roles in bulk-tissue biomechanics), investigating mechanical/biochemical modifications to networked type II collagen, and proposing, calibrating, and validating constitutive models for finite element analyses. Highlights: We established a protocol for microtensile testing of networks of type II collagen. Digestion with 0.5 mg/mL trypsin for 18 h removes >95% of PG without damaging COL. Specimen shape ensures homogeneous stresses in gauge region in uniaxial extension. Specimen thickness (140–160 μ m) ensures mechanical results independent of thickness. Strain rate (1.5–60%/min) ensures mechanical results independent of strain rate.